(untitled) (International Journal of Applied Research in Management and Economics, 2023)
Customer loyalty and satisfaction are crucial for the success, prosperity and survival of a business. However, customers’ preferences differ according to their attitudes towards products and services, as well as the culture and conditions in which they live, which can influence their preferences when choosing a business. More than 90% of all businesses are small and medium-sized enterprises, and about 50% of private businesses in Europe and 80% in Africa are family businesses. These businesses are considered the engine of economic development and growth and are instrumental in job creation. However, if these businesses were not favoured by their customers, they would have no chance to survive and fight poverty, which is typical of African countries. Our study, therefore, identifies and compares what type of company customers from developing countries (represented by the Mbulu region, Tanzania) prefer and whether their preferences are similar compared to respondents from more developed countries (represented by Liberec, Czech Republic). By testing several hypotheses, a dependency was found between customers’ attitudes when choosing a company and their place of origin. African respondents prefer large non-family businesses to small or medium-sized family businesses, while European respondents prefer small or medium-sized family businesses.